Challenges and prospects of Chinese language post-covid-19 pandemic - Rudiansyah; Julina (Universitas Negeri Malang, 2023)
The Covid-19 pandemic has an impact on the world of education, including higher education. The existence of this corona virus outbreak hinders teaching and learning activities that usually take place face-to-face. Even so, this pandemic was able to accelerate education 4.0. The learning system is carried out remotely by utilizing information technology. As time goes by, Mandarin is believed to be the second language in the world. The entry of Mandarin into Indonesia was marked by the 1998 Reformation incident, in which suddenly Mandarin began to mushroom in many places. The prospects and challenges of Mandarin, including other foreign languages, are regulated in the National Language Politics and National Language Policy. However, in its implementation in society, it is still running as if without direction. This paper is entitled 'Challenges and Prospects of Chinese Language Post-Covid-19 Pandemic'. This paper aims to provide insight and fresh air related to post-pandemic Mandarin learning. The research method used is a qualitative method and is presented starting from the descriptive, analytical, and comparative stages. The results of this study are information about the prospects and challenges of learning Mandarin in Indonesia after the Covid-19 pandemic.